Growing up in culture gambling explaining adolescent students' academic performance using the theory of planned behavior. - Burgos, Jaclyn Gay S.
Integrating Icek Ajzen?s Theory of Planned Behavior, this study seeks to explain the factors that influence the academic performance of adolescent students. In assessing the academic performance: questionnaires for attitudes towards behavior, subjective norm, perceived behavioral control, and intention were administered to adolescent students (n=88) in rural areas of Iloilo. A Pearson-product moment correlation was used to examine the correlation between the factors and academic performance. There were five participants who joined the focus group discussion and their answers provided an in-depth connection of the variables. Results of the quantitative analysis stated that attitude towards behavior, subjective norm, and perceived behavioral control are individually correlated with intention but only attitude towards behavior is significantly correlated with academic performance. The results from this study can be used in schools and related government agencies in shaping students to have a more positive outlook with regards to academic performance.